2009
DOI: 10.1007/s12517-009-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Jizan shelf sediments, southern Red Sea coast of Saudi Arabia

Abstract: Surface sediments from the Jizan shelf, southern Red Sea, were analysed for grain size and mineralogical and elemental composition in order to establish their geochemical characteristics. Texturally, sediments are classified into sand and mud; the latter dominates the shelf. Grain size variability and mineralogical assemblages present in the sediments largely control the abundance and distribution of CaCO 3 , organic carbon content (OC) and the major and trace elements. Sand sediments are composed of carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 25 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In the framework of the multi‐proxy approach used, the extraction of significant stratigraphic patterns from thousands of data points is performed through statistical methods (e.g. Chen et al ., ; Basaham, ; Dias et al ., ; Monien et al ., ). The use of a rigorous statistical framework, including linear correlations, principal component analysis, hierarchical cluster analysis and variogram computation allows for an integrated and quantitative assessment of the complete geochemical dataset.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of the multi‐proxy approach used, the extraction of significant stratigraphic patterns from thousands of data points is performed through statistical methods (e.g. Chen et al ., ; Basaham, ; Dias et al ., ; Monien et al ., ). The use of a rigorous statistical framework, including linear correlations, principal component analysis, hierarchical cluster analysis and variogram computation allows for an integrated and quantitative assessment of the complete geochemical dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The shallow water carbonate deposits comprise mainly of biogenic sand enriched in calcareous algae, coral debris, skeletons remain of molluscs, and foraminiferal tests (Bahafzallah and El-Askary, 1981;Behairy, 1984, 1986;Basaham, 2009;Al-Dubai, 2011;Bantan and Abu-Zied, 2014). Chemical and biochemical carbonate deposits also take place in the coastal hypersaline shallow areas (Winter et al, 1983;Ellis and Milliman, 1985;Basaham, 2009). Wright and Burchette (1996) reported that carbonate deposits are very frequent and consist of biogenic carbonate (detrital bioclastics and non-detrital calcareous organisms), peloids, coated grains (e.g., ooids), aggregates, lithified clastics and matrix (mud-grade carbonate).…”
Section: Introductionmentioning
confidence: 99%